Characterization of Kanthal APMT and T91 oxidation at beyond design-basis accident temperatures. (15th July 2020) - Copeland-Johnson, Trishelle M.; Nyamekye, Charles K.A.; Gill, Simerjeet K.; Ecker, Lynne; Bowler, Nicola; Smith, Emily A.; Rebak, Raul B.
Graphical abstract: Highlights: APMT and T91 exposed to air and steam at 1200 °C for 2 h. APMT formed α-Al2 O3 layer that was thicker after exposure to air than steam. T91 formed mixed, non-passivating Fe-Cr layer in both environments. Major oxidation products in T91 are Fe3 O4, FeO and Fe(3-x) Crx O4 . Abstract: Limited information is available on the oxidation mechanism of accident tolerant claddings (ATC) Kanthal APMT and T91 at the onset of beyond design-basis accident (BDBA) conditions. We characterized the surface of these ATC alloys after steam and air exposure at 1200 °C for 2 h, defining the oxidation mechanism. Thickness and composition were analyzed with microscopy, Raman spectroscopy, and synchrotron diffraction. Our results demonstrate that APMT forms a compact and homogeneous α-Al2 O3 layer when exposed to air or steam. T91 forms a heterogeneous porous layer, containing a mixture of Cr- and Fe-based oxides, whose composition changes with the exposure environment.